Divalent Ion Selectivity in Capacitive Deionization with Vanadium Hexacyanoferrate: Experiments and Quantum‐Chemical Computations. (18th July 2021) - Singh, Kaustub; Li, Guanna; Lee, Juhan; Zuilhof, Han; Mehdi, B. Layla; Zornitta, Rafael L.; de Smet, Louis C. P. M.
Abstract: Selective removal of ions from water via capacitive deionization (CDI) is relevant for environmental and industrial applications like water purification, softening, and resource recovery. Prussian blue analogs (PBAs) are proposed as an electrode material for selectively removing cations from water, based on their size. So far, PBAs used in CDI are selective toward monovalent ions. Here, vanadium hexacyanoferrate (VHCF), a PBA, is introduced as a new electrode material in a hybrid CDI setup to selectively remove divalent cations from water. These electrodes prefer divalent Ca 2+ over monovalent Na +, with a separation factor, βCa/Na ≈3.5. This finding contrasts with the observed monovalent ion selectivity by PBA electrodes. This opposite behavior is understood by density functional theory simulations. Furthermore, coating the VHCF electrodes with a conducting polymer (poly‐pyrrole, doped with poly‐styrenesulphonate) prevents the contamination of the treated water following the degradation of the electrode. This facile and modular coating method can be effortlessly extended to other PBA electrodes, limiting the extent of treated water contamination during repeated cycling. This study paves the way for tunable selectivity while extending the library of electrodes that can be successfully used in (selective) CDI. Abstract : This study presents a new vanadium‐based Prussian blue analog (PBA) as an electrode material in capacitive deionization that is selective towards divalent over monovalent cations, unlike the usual monovalent selectivity reported with PBAs. This selectivity is explored experimentally and theoretically via quantum‐chemical simulations. The results are a proof of concept for tuning ion selectivity by changing the chemical composition of PBAs.